Foreword. The Baltic Way - David Ramiro Troitino (Pasado y Memoria)
The dossier presented here aims to scientifically analyse the role of citizens in the fight against totalitarianism, as an example of Europeanism and collective effort toward a better society—a reminder of the struggle for freedom and a balanced society in the face of an external adversary that had mercilessly occupied the region for decades.